Are sutureless and rapid-deployment aortic valves a serious alternative to TA-TAVI?: A matched-pairs analysis - Maisary, Sameer al-; Farag, Mina; Gussinklo, Willem Hendrik te; Kremer, Jamila; Pleger, Sven Torsten; Leuschner, Florian; Karck, Matthias; Szabó, Gábor; Arif, Rawa (Journal of Clinical Medicine, 2021)
Background: Transcatheter aortic valve implantation is a feasible alternative to conventional aortic valve replacement with expanding indication extending to low-risk patients. Sutureless and rapid-deployment aortic valves were developed to decrease procedural risks in conventional treatment. This paired-match analysis aims to compare patients undergoing surgical transcatheter aortic valve implantation to sutureless and rapid-deployment aortic valve implantation. Methods: Retrospective database analysis between 2010 and 2016 revealed 214 patients undergoing transcatheter aortic valve implantation procedures through surgical access (predominantly transapical) and 62 sutureless and rapid-deployment aortic valve procedures including 26 patients in need of concomitant coronary artery bypass surgery. After matching, 52 pairs of patients were included and analyzed. Results: In-hospital death (5.8% vs. 3.8%; p = 0.308) was comparable between transcatheter aortic valve implantation (mean age 77 ± 4.3 years) and sutureless and rapid-deployment aortic valve implantation groups (mean age 75 ± 4.0 years), including 32 females in each group. The logistic EuroSCORE was similar (19 ± 12 vs. 17 ± 10; p = 0.257). Postoperative renal failure (p = 0.087) and cerebrovascular accidents (p = 0.315) were without significant difference. The incidence of complete heart block requiring permanent pacemaker treatment was relatively low for both groups (1.9% vs. 7.7%; p = 0.169) for TAVI and sutureless and rapid-deployment valves respectively. Intraoperative use of blood transfusion was higher in the sutureless and rapid-deployment aortic valve implantation group (0.72 U vs. 1.46 U, p = 0.014). Estimated survival calculated no significant difference between both groups after 6 months (transcatheter aortic valve implantation: 74 ± 8% vs. sutureless and rapid-deployment aortic valve implantation: 92 ± 5%; log rank p = 0.097). Conclusion: Since sutureless and rapid-deployment aortic valve implantation is as safe and effective as transapical transcatheter aortic valve implantation, combining the advantage of standard diseased-valve removal with shorter procedural times, sutureless and rapid-deployment aortic valve replacement may be considered as an alternative for patients with elevated operative risk considered to be in the “gray zone” between transcatheter aortic valve implantation and conventional surgery, especially if concomitant myocardial revascularization is required.